Disseminated Penicillium marneffei infection diagnosed on examination of a peripheral blood smear of a patient with human immunodeficiency virus infection - Supparatpinyo K. (2014)
We describe a case of disseminated Penicillium marneffei infection in a patient infected with human immunodeficiency virus. The diagnosis was made by examination of a peripheral blood smear. The patient presented with fever, jaundice, generalized lymphadenopathy, hepatosplenomegaly, and an erythematous, papular rash. Microscopic examination of a Wright's-stained peripheral blood smear revealed many yeast cells in neutrophils. Some yeast cells had clear central septation. Presumptive diagnosis of disseminated P. marneffei infection was made, and treatment was started several days before the culture results were available.